Pragmatic Trials in Long‐Term Care: Research Challenges and Potential Solutions in Relation to Key Areas of Care. Issue 3 (23rd February 2022) - Resnick, Barbara; Zimmerman, Sheryl; Gaugler, Joseph; Ouslander, Joseph; Abrahamson, Kathleen; Brandt, Nicole; Colón‐Emeric, Cathleen; Galik, Elizabeth; Gravenstein, Stefan; Mody, Lona; Sloane, Philip D.; Unroe, Kathleen; et al.
Abstract: As a method of research, pragmatic trials are recommended so as to generate results that are applicable to real‐world care. This intent is especially important for the millions of older adults who receive long‐term care in thousands of nursing homes and assisted living communities across the country—and many millions more around the globe. This article presents key points raised by experts participating in a conference funded by the National Institute of Aging held at the 2021 conference of the Society for Post‐Acute and Long‐term Care Medicine. The purpose of the conference was to convene leading clinicians, researchers, and industry partners to address special considerations of pragmatic trials in long‐term care. Cross‐cutting and unique challenges and solutions to conducting pragmatic trials were discussed focusing on 3 areas of clinical relevance to long‐term care: (1) functional care and outcomes, (2) psychosocial care and quality of life, and (3) medical care and outcomes, with a special focus on persons with dementia. Challenges and innovative solutions were organized across the 9 domains of the revised Pragmatic‐Explanatory Continuum Indicator Summary (PRECIS) Tool, and future research recommendations for pragmatic trials in long‐term care were identified. Abstract : See related editorial by Zimmerman et al . and Special Articles by Gurwitz et al . and Levy et al . in this issue.